PEMAKAIAN BAHASA INDONESIA (KATA) DALAM SURAT RESMI/DINAS KELUAR DESA KESIMAN KERTALANGU KECAMATAN DENPASAR TIMUR DENPASAR (STUDI KASUS) - I Nengah Mileh (Universitas Warmadewa, 2019)
[The Use of Indonesian Language (Word) in the Official Letter / Outgoing Mail of Kesiman Kertalagu Village, East Denpasar Sub District, Denpasar] This research entitled